Lathyrol affects the expression of AR and PSA and inhibits the malignant behavior of RCC cells - Song Shengyou; Tai Lunwei; Zhou Lei; Jiang Junling; Zhao Junfeng (Open Medicine)
To investigate how lathyrol affects aggressive behaviors and related proteins of the androgen receptor (AR) 786-O cells.